X-Ray fluorescence as a method of characterizing inorganic pigment patterns in the work of Julian Onderdonk - Christopher Dostal (Heliyon, 2023)
This study utilized portable X-Ray fluorescence to analyze pigment patterns in 33 paintings by Julian Onderdonk, a 19th-20th century Texas impressionist. This analysis led to the identification of distinctive pigment preferences for Onderdonk at different periods of his career. Using the pigment preference patterns identified in the paintings that were dated by the artist, undated works were analyzed and assigned to different periods in the artists career based on their pigment patterns. This study represents a non-destructive method for organizing the artist's work without solely relying on stylistic changes.